If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(3/8)*y-7 = (-5/8)*y // - (-5/8)*y
(3/8)*y-((-5/8)*y)-7 = 0
(3/8)*y+(5/8)*y-7 = 0
y-7 = 0 // + 7
y = 7
y = 7
| 2y+(-2y)= | | 18*2/5 | | 5(x+3)=9x-11 | | 32×1/4 | | 7/10(190) | | -4(-5+m)=-8 | | f(8)=-1 | | g(x)=0.5x+13 | | 4+tanx=4 | | .9y=1.2x+72 | | Y=4-3*4/3 | | 4-3*-4/3 | | 4(x-5)=-20+4x | | p(p-.105)=5907 | | ×/9-15=15 | | 7y-3=6y+3 | | 4(x+6)-8x=-8 | | -4(n-2)=32 | | m^3+10m+9=0 | | 19/4x≤17 | | p(p+.105)=5907 | | 2a-11=8a+18 | | -8/-6 | | 221/2X101/4 | | p(.105)=5907 | | x^2+11x+76=0 | | 2x+5(x-2)=6 | | g(x)=2x^2+3 | | 16d+(4+-5d)=-67 | | x^2-3x+63=0 | | 3x+(-8)=1 | | 5ln(y)-5ln(y+0.2)= |